Neuroendocrine Regulation over Gonad Development and Growth of Secondary Sexual Organs in Freshwater Crab, Barytelphusa cunicularis (Westwood-1836, Decapoda, Potamonidae) - Patil Meena, R.F. Pathre* (Recent Research in Science and Technology, 2011)
Neuroendocrine control over development of gonads and secondary sexual organs was studied in Barytelphusa cunicularis, collected from backwaters of Jayakwadi Dam. Male and female were divided equally into different groups and length of pleopod and abdomen in female and chela in male, measured before start and at the end of experiment. Eyestalk of both male and females were removed and both were administrated with extract of eyestalk, brain and thoracic extract hormones. When eyestalks were removed both in male and female the ovarian weight and testicular weight increased that increase was due to increase in number of oocytes and seminiferous tubules. Eyestalk removal also stimulated growth of abdomen, pleopod and chela in both sexes. Administration of eyestalk hormone resulted into inhibition of spermatogenesis and oogenesis. Male and females administrated with brain, thoracic ganglion hormone showed promotion over gonadal development and growth of secondary sexual organs, pleopod, abdomen and chela was also reported. Effect on secondary sexual organs was much by brain hormones when compared with others, suggesting presence of some factors. In Barytelphusa cunicularis, eyestalk has inhibitory principle of gametogenesis, whereas brain and thoracic ganglion hormones have stimulatory principles.